1500. At Risk Drinking Is Common Among HIV-Infected Department of Defense (DoD) Beneficiaries But Was Not Associated with Prevalent GC/CT Infections. (26th November 2018) - Ganesan, Anuradha; Wang, Xun; Blaylock, Jason M; Okulicz, Jason; Waggoner, Sandra; Johnson, Brian; Kirkland, Nichol; Wimberly, Veronica; Garges, Eric; Deiss, Robert
Abstract: Background: At-risk drinking and sexually transmitted infections (STIs) are both common among HIV-infected patients. Nearly 50% of subjects in the US Military Natural History Study (NHS), a cohort of HIV-infected DoD beneficiaries, report alcohol misuse. Nonetheless, few studies have examined whether at-risk drinking, a modifiable risk factor, is associated with STIs in this population. We examined the relationship between alcohol use and prevalent gonorrhea (GC) and chlamydia (CT) infections. Methods: Consented NHS subjects underwent genitourinary (GU) and extragenital nucleic acid amplification testing (NAAT) for GC/CT infections and responded to a behavioral survey to describe substance use and sexual risk. At-risk drinking was defined as consumption of >4 drinks/day or 14 drinks/week. Logistic regression was used to examine the association of at risk drinking and GC/CT infections. Results: A total of 472 men were included with a median age of 41 years (IQR 31, 51); 44% were African American. Male sexual partners were reported by 90%. At-risk drinking (54%) and having sex while drunk in the last 6 months (21%) was commonly reported. Overall, 15% ( n = 70) had either GC or CT infection. With respect to anatomic site, 11% had anorectal infections (GC = 4%; CT = 7%), 5.3% had pharyngeal infection (GC 3.8%; CT −1.4%) and, 2.3% had GU infection (GC 0.6%; CT 1.7%). In univariate analysis, younger age, multiple male sexual partners, having sex while drunk, and concurrent partnership were associated with STI diagnosis. In the adjusted model, multiple male partners and concurrent sex remained significant (see table). Conclusion: At-risk drinking remains common in the NHS; however, it was not associated with GC/CT infections. We observed a high prevalence of GC/CT infection, emphasizing the importance of ongoing screening of this high-risk population. Although strategies to reduce alcohol use are unlikely to reduce STIs in our population, these strategies are necessary to reduce other adverse health consequences associated with alcohol use. Disclosures: All authors: No reported disclosures.